Pelatihan Keterampilan Menulis Teks Hikayat Berbasis Video Animasi dan Latihan Terbimbing pada Siswa Kelas X SMA Negeri 5 Padang - Zulfitriyani; Ria Satini; Iswadi Bahardur; Asri Wahyuni Sari; Sri Mulyani Rusli (CV Abid Abadi Jaya, 2026)
Classical literature learning, particularly hikayat texts, often faces serious challenges in schools as it is perceived as obsolete, abstract, and heavily reliant on difficult archaic language for the digital generation. This issue was observed among tenth-grade students at SMA Negeri 5 Padang, who experienced linguistic and structural barriers, resulting in writing compositions that failed to meet the minimum mastery standards. On the other hand, teachers still tended to use conventional, one-way methods without utilizing innovative media. This community service program aims to enhance students' hikayat text-writing skills through the intervention of the Guided Writing method based on a process approach, synergized with audio-visual media in the form of hikayat animated videos. The target audience for this program was 70 tenth-grade students of SMA Negeri 5 Padang. The implementation method involved intensive training and mentoring over two sessions within a one-month period, covering the stages of planning, translating, and reviewing story drafts. The results demonstrated a highly significant increase in students' literacy and cognitive abilities. The student mastery target in producing complete hikayat texts jumped drastically to 90% (above the minimum mastery criteria). The use of animated videos effectively reduced students' working memory load in visualizing palace settings , while the distribution of Creative Glossaries successfully mitigated archaic language barriers. In addition to producing a tangible output in the form of an E-Book Anthology of Contemporary Hikayat Texts , this program successfully internalized didactic character values and revitalized students' appreciation for Nusantara's cultural roots.